2023
DOI: 10.1038/s41598-023-33777-w
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid multi-particle approach to range assessment-based treatment verification in particle therapy

Abstract: Particle therapy (PT) used for cancer treatment can spare healthy tissue and reduce treatment toxicity. However, full exploitation of the dosimetric advantages of PT is not yet possible due to range uncertainties, warranting development of range-monitoring techniques. This study proposes a novel range-monitoring technique introducing the yet unexplored concept of simultaneous detection and imaging of fast neutrons and prompt-gamma rays produced in beam-tissue interactions. A quasi-monolithic organic detector a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…by the prompt-gamma imaging [11], spectroscopy [12], timing [13] and peak-integration [14] methods. It has also been shown that the spatial distribution of fast neutrons (FNs) generated during treatment delivery is correlated to the proton range, and could reveal complementary information to PGs about the proton range [15,16]. To exploit this, the NOVO (NeutrOn and gamma ray imaging for real-time range VerificatiOn and image guidance in particle therapy) project was initiated with the goal of imaging the proton range using information from both PGs and FNs simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…by the prompt-gamma imaging [11], spectroscopy [12], timing [13] and peak-integration [14] methods. It has also been shown that the spatial distribution of fast neutrons (FNs) generated during treatment delivery is correlated to the proton range, and could reveal complementary information to PGs about the proton range [15,16]. To exploit this, the NOVO (NeutrOn and gamma ray imaging for real-time range VerificatiOn and image guidance in particle therapy) project was initiated with the goal of imaging the proton range using information from both PGs and FNs simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Such a hybrid imaging system promises to reduce range uncertainties and improve treatment outcomes by exploiting the increased statistics and complementary information from both particle species. Simulation studies have shown that such a system is capable of imaging range deviations of 1 mm at proton intensities as low as 6.08 (21) • 10 6 protons/spot by using combined information from PGs and FNs [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations